Landlocked countries in South America : transport system challenges - Wilmsmeier, Gordon (UN ECLAC SantiagoCL, 2009)
Analyses the current state of the landlocked developing countries (LLDCs), Bolivia and Paraguay viz, infrastructure at national level and connectivity towards adjacent countries; recent developments in international law and treaties and; cross-border operation.. Evaluates the level of international transport costs and potential impact on trade. Presents the currently induced over costs in logistic chains, which pose an additional burden to the competitiveness of the countries.